Aliocha Dostoevski’s death during an epileptic seizure - Edson José Amâncio; Pedro André Kowacs; Bruno Toshio Takeshita; Fábio Augusto Nascimento; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
ABSTRACT Mortality due to epilepsy is of great concern worldwide. Individuals with epilepsy have a two- or three-fold risk of death when compared to the general population. Based on biographical data and Anna Grigoriévna Dostoevskaia’s memories, the authors concluded that a prolonged episode of status epilepticus was the culprit in the death of young Aliocha, youngest son of Fyodor Mikhailovich and Anna Dostoevski. At the time of Aliocha’s death, very limited knowledge about epilepsy or therapeutic resources was available. Despite all the progress, epilepsies remain potentially fatal conditions. The suffering generated by Aliocha’s death and other similar cases remains as a challenge for epileptologists who assemble efforts to fight against such conditions.